Molecular diagnosis and successful doxycycline therapy of Mycoplasma felis infection in a domestic short hair cat - Kusumawati , Nindya (ARSHI Veterinary Letters, 2025)
Feline upper respiratory tract infections (URTIs) are among the most prevalent illnesses in domestic cats, often presenting with overlapping clinical signs regardless of the causative pathogen. Accurate identification of the etiological agent is essential for targeted therapy and improved clinical outcomes. This case report aims to describe the clinical presentation, diagnosis, and successful treatment of a domestic short hair cat with respiratory infection caused solely by Mycoplasma felis. A 10-month-old female domestic short hair cat from Sidoarjo, East Java, Indonesia, presented with a one-week history of sneezing and purulent nasal discharge. Physical examination revealed conjunctivitis and fever (39.8 °C). Polymerase chain reaction (PCR) assays targeting common feline respiratory pathogens—Feline herpesvirus-1, Feline calicivirus, Chlamydia felis, and Mycoplasma felis (M. felis)—were conducted using nasal swabs. PCR analysis yielded a positive result only for M. felis. Hematological analysis revealed leukocytosis and marked neutrophilia, supporting the presence of bacterial infection. The cat was treated with oral doxycycline at 10 mg/kg once daily for 42 days. Clinical signs resolved progressively, and post-treatment PCR confirmed the absence of M. felis. This case highlights the importance of molecular diagnostics in feline respiratory infections and demonstrates the effectiveness of doxycycline as a first-line treatment for M. felis-associated URTI.